INTERNALISASI NILAI-NILAI SPIRITUAL SEBAGAI FONDASI PSIKOLOGIS PEMBELAJARAN: Telaah Psikologi Islam Terhadap Pembentukan Jiwa Pembelajar) - Khasnah Syaidah (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
Islamic education in Indonesia faces multifaceted challenges in the globalized era, particularly concerning the integration of spiritual values within formal educational systems. The study originates from concerns about the declining role of spiritual dimensions in education, overshadowed by cognitive-dominated approaches and materialistic cultural pressures. This research identifies key constraints in implementing Islamic education and explores strategic opportunities for transforming the learning process grounded in spiritual and character values. A reflective qualitative method was applied through a narrative synthesis of diverse perspectives on contemporary Islamic education, including concepts such as tarbiyah nafs, Islamic learning psychology, and institutional practices in Indonesia. Thematic analysis was employed to investigate both the challenges and the innovative prospects relevant to the local sociocultural context. Findings reveal significant potential for Islamic education to foster character development by revitalizing spiritual traditions, leveraging digital technologies for spiritual learning, and strengthening the role of educators as spiritual exemplars. Despite persistent issues such as curriculum fragmentation, student motivation crises, and external value pressures, opportunities for reform remain wide open. These include pedagogical innovations and collaborative engagement among stakeholders. Islamic education in Indonesia can evolve as a pillar of social transformation—one that enlightens minds while purifying souls.